Design and development of an Early Warning System For Railway Level Crossings with arrival detection and speed monitoring based on Arduino Uno and Inductive Proximity Sensor - Arief Darmawan; Trinil Muktiningrum (Politeknik Perkeretaapian Indonesia Madiun, 2025)
Railway level crossings are critical safety points prone to accidents, necessitating a reliable Early Warning System (EWS) to protect road users. This study designs and evaluates an EWS integrating Arduino Uno and inductive proximity sensors to detect train arrivals and monitor train speed at a level crossing in Blitar Regency. Field experiments were conducted with sensors installed at an optimal maximum distance of 30 mm from the train wheel flange. Over a five-day period, the sensors achieved a wheel detection success rate of approximately 99.95%, while the speed counting system showed an accuracy of 87.22% compared to GPS tracking data. The 12.78% deviation in speed measurement falls within acceptable tolerance limits according to international standards on measurement uncertainty and railway electromagnetic compatibility. Performance decreased significantly beyond the 30 mm threshold, confirming the recommended installation distance. Compared to existing systems, this approach demonstrates improved modularity and algorithmic flexibility that enable future accuracy enhancements. Routine maintenance and regular calibration are essential to sustain system stability. Future work will focus on algorithm development for enhanced train speed calculation precision and expanded testing under